Dothiorella saprophytica sp. nov.: a new Dothiorella sexual morph from Thailand - Farias, Antonio Roberto Gomes De; Louangphan, Johnny; Afshari, Naghmeh (Phytotaxa, 2023)
Dothiorella has cosmopolitan species and a wide range of hosts as endophytes, saprobes, and pathogens. Many species have been introduced solely based on their host association, resulting in misidentification. This study describes a novel species, Dothiorella saprophytica sp. nov., a sexual morph of Dothiorella, from Chiang Mai, Thailand using multi-locus phylogeny (ITS + tef1-α + β-tub) and morphological characters. Detailed morphology and multi-locus phylogeny are provided to give more insights into the diversity and taxonomy of this genus. Dothiorella saprophytica is characterized by its sexual morph with pseudothecial and immersed ascomata, peridium textura angularis, hyaline, thin-walled, unbranched, and septate pseudoparaphyses, clavate and bitunicate asci, and ovoid to sub-clavate, 0–1-septate ascospores. Introducing new fungal species, such as D. saprophytica sp. nov., adds to our understanding of biodiversity and the ecology of fungi and provides opportunities for further research.